Financial stability in Europe: Banking and sovereign risk - Brůha, Jan; Kočenda, Evžen (Journal of Financial Stability, 2018)
We analyze the link between banking sector quality and sovereign risk in the whole European Union over 1999–2014. We employ four different indicators of sovereign risk (including market- and opinion-based assessments), a rich set of theoretically and empirically motivated banking sector characteristics, and a Bayesian inference in panel estimation as a methodology. We show that a higher proportion of non-performing loans is the single most influential sector-specific variable that is associated with increased sovereign risk. The sector’s depth provides mixed results. The stability (capital adequacy ratio) and size (TBA) of the industry are linked to lower sovereign risk in general. Foreign bank penetration and competition (a more diversified structure of the industry) are linked to lower sovereign risk. Our results also support the wake-up call hypothesis in that markets re-appraised a number of banking sector-related issues in the pricing of sovereign risk after the onset of the sovereign crisis in Europe.